Resistensi Quraisy terhadap Gerakan Monoteisme: Analisis Historis Periode Makkah - Shale Afif (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2026)
This article analyzes the forms and dynamics of the resistance of the Quraisy against the monotheistic movement brought by the Prophet Muhammad during the Meccan period (610–622 CE). The study focuses on the social, economic, political, and religious factors underlying the rejection of the Quraysh elite toward the preaching of tawhid, as well as its implications for the formation of the early Muslim community. This research employs the historical research method, including the stages of heuristics, source criticism, interpretation, and historiography. Primary sources consist of classical sīrah literature and hadith, while secondary sources include modern historiographical works on seventh-century Mecca. The findings indicate that Quraysh resistance was not solely driven by theological differences, but also by perceived threats to the stability of the tribal social structure, the religious authority of the custodians of the Ka‘bah, and the economic interests of Meccan trade. The monotheistic movement was seen as potentially undermining the symbolic and material legitimacy that sustained Quraysh dominance. Despite facing intimidation, boycott, and violence, the Muslim community experienced stronger ideological consolidation. Thus, Quraysh resistance became a significant factor in shaping the theological character and social solidarity of early Islamic civilization in the Meccan phase.